Role of non-governmental organizations in post-relocation support of reservoir migrations in China: a just transition perspective - Hong, Xueqing; Chen, Shaojun; Sun, Jingcheng (Frontiers in Environmental Science, 2023)
In recent decades, energy transition has been a major structural change worldwide to replace fossil fuels. Hydropower is a valuable renewable energy source which can mitigate the electricity demand of livelihoods and help to achieve the target of carbon neutrality goals. However, owing to the hydropower construction, involuntary resettles are suffering with land and socio-economic security. Nongovernmental organizations (NGOs) play a vital role in promoting a just transition for reservoir migrants. The present study examines the work of local NGOs in a reservoir resettlement area in China through semi-structural interviews, and participant observations followed by qualitative analysis. Study explores how the NGOs organize reservoir migrants to participate in post-relocation support (PReS) projects. The study finds that the organized participation of reservoir migrants in PReS is the key process required to achieve a just transition. Moreover, NGOs ensure that all affected reservoir migrants have equal access to development opportunities through the three linked levels of co-construction, co-management, and co-sharing through the elitedriven establishment of benefit linkages and fair benefit distribution, and ultimately achieve a standard of living for migrants. Organized participation improves the equity and sustainability of benefits for reservoir migrants, but organizing reservoir migrants requires firm support from the local, regional and national governments, and the trust of migrants in local NGOs. Findings further stated that the PRes policy still has some blank spot, therefore, it is necessary to frame robust policy frameworks to restore the livelihoods of reservoir migrants.